Genotyping of Mycobacterium avium subsp. avium isolates from domestic animals in Slovenia by IS901 RFLP - M. Pate; M. Moravkova; B. Krt; I. Pavlik; M. Ocepek (Veterinární Medicína, 2009)
ABSTRACT: Apart from birds, Mycobacterium avium subsp. avium (MAA) is often isolated from granulomatous lesions in pigs and occasionally from cattle and other animals. The objectives of this study were the detection of IS901 restriction fragment length polymorphism (RFLP) types of MAA isolates from different species of domestic animals between the years 1998 and 2004 and the comparison of the detected RFLP types with previously described RFLP types collected in the database of the OIE Reference Laboratory for Avian Tuberculosis (Brno, Czech Republic). Furthermore, the RFLP types of the isolates obtained from MAA outbreaks on one of the largest pig farms in Slovenia were also investigated. A total of 62 isolates (56 from pigs, five from poultry and one from cattle) were identified with IS901 PCR and IS901 RFLP typed using restriction endonucleases PvuII and PstI. Seven PvuII RFLP and 11 PstI RFLP types resulted in 12 combined PvuII PstI types; none of these matched the combined RFLP types described in previous studies. Our contributions to the database were two new PvuII and eight new PstI RFLP types. Identical RFLP types were found among isolates of animals originating from individual farms. Finding of identical RFLP types within a farm is not surprising because the animals were epidemiologically related and infected with one strain. A unique RFLP type F-A17 was detected in isolates from different pig herds and also in isolates from poultry. Detection of identical RFLP types on different farms may reflect one MAA source. The other combined PvuII PstI RFLP types were identified only once which indicates considerable variety of MAA RFLP types in Slovenia.